Pengaruh ROA, ROE, dan EPS Terhadap Harga Saham Perbankan Buku III Yang Tercatat di BEI - Kenisha Arvianetta Sutantio; Amelia Setiawan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The investment in the capital market is currently increasing among the public, emphasizing the urgency of providing financial literacy to enable individuals to make informed and intelligent investment decisions in the capital market. BUKU III was selected due to the relatively low per-share stock prices of the existing banks, allowing the public to have higher purchasing power. ROA, ROE, and EPS were chosen as the factors under review due to their widespread availability in financial reports, serving as a reference for the public in determining their investment choices. Previous studies focused on the impact of ROA, ROE, and EPS on stock prices in the BUKU IV (Tahir, Djuwarsa, and Mayasari, 2021). Their findings revealed that ROA had no significant independent influence on stock prices. Conversely, ROE and EPS, independently, significantly influenced stock prices in BUKU IV banks. Additionally, the simultaneous impact of ROA, ROE, and EPS affected the stock prices of BUKU IV banks. This study aims to explore whether ROA, ROE, and EPS exert influence on the BUKU III banks stock prices listed on the Indonesia Stock Exchange. The research method employed is the hypotheticodeductive method, utilizing quarterly data from 2018 to 2022, with a sample size of 5 companies. Data were collected from Stockbit, and the analysis methods used included t-tests, F-tests, and multiple linear regression analysis using Microsoft Office Excel and SPSS tools. The results indicate that ROA, ROE, and EPS do not have a partial or simultaneous impact on the stock prices of BUKU III banks.